PKM PENGUATAN LITERASI NUMERASI SISWA SD MELALUI PELATIHAN MEDIA DIGITAL PADA KELOMPOK IBU BELAJAR MATEMATIKA - Wakit, Ahmat; Hidayati, Nor; Wahono, Buang Budi; Arif, Muhammad Nor; Fauziah, Atha (Politeknik Perkeretaapian Indonesia Madiun, 2025)
This community service program is in the form of training and mentoring for the Mathematics Learning Mothers Community (KIBM) of Kerso Village. This community service was carried out in the odd semester of the 2024/2025 academic year. KIBM is a group of mothers who have children who are undergoing elementary education or equivalent. The purpose of KIBM is to improve the basic mathematics skills of KIBM, the level of parental confidence in accompanying children in learning, increase parental involvement in accompanying children and improve numeracy literacy skills. The implementation methods used include preparation, socialization, training, and evaluation. The results achieved from this activity are the basic mathematics skills of the mathematics learning mothers group increased, the mothers' confidence in guiding their sons and daughters' learning increased, the involvement of mothers in accompanying children in learning increased, and the implementation of training can improve numeracy literacy skills.